ASSESSMENT OF CANDIDA ALBICANS ADHERENCE TO PARTIAL REMOVABLE DENTURE FRAMEWORK SURFACES - Elena-Raluca Baciu; Sorana Nicoleta Roșu; Iulian-Costin Lupu; Alice Murariu; Norina Consuela Forna (Romanian Journal of Oral Rehabilitation)
Aim of the study This study aimed to evaluate the adhesion of Candida albicans to cobalt-chromium-molybdenum (Co-Cr-Mo) removable partial denture (RPD) frameworks subjected to different surface treatments, and to assess the antifungal susceptibility of the isolated strains. Materials and Methods A total of 52 RPDs were fabricated for 34 patients and divided into two groups based on surface finishing: mechanical polishing only and combined mechanical-electrolytic polishing. Surface roughness measurements were conducted prior to clinical use. Microbiological samples were collected after patient wear, cultured on CHROMagar Candida medium, and subjected to antifungal susceptibility testing against five antifungal agents. Results RPDs treated with mechanical polishing alone exhibited significantly higher surface roughness compared to those subjected to both mechanical and electrolytic polishing (p < 0.001). Higher surface roughness was associated with increased Candida albicans colonization (p = 0.005). Most Candida albicans strains remained susceptible to standard antifungal agents, although minor resistance to miconazole was observed. Conclusions Surface finishing significantly influences Candida albicans adhesion to Co-Cr-Mo RPD frameworks. Combined mechanical and electrolytic polishing effectively reduces surface roughness and microbial colonization. These findings highlight the importance of optimizing surface treatments to minimize prosthesis-related infections and support better clinical outcomes.